2018
DOI: 10.1007/s11356-018-2892-3
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the sources of suspended sediment and particle-bound trace metal elements in an urban catchment coupling elemental and isotopic geochemistry, and fallout radionuclides

Abstract: The excessive supply of contaminants from urban areas to rivers during the last centuries has led to deleterious impacts on aquatic ecosystems. The sources, the behavior, and the dynamics of these contaminants must be better understood in order to reduce this excessive anthropogenic pollution. Accordingly, the current research investigated the particle-bound trace element (TE) contamination of the 900-km2 Orge River (Seine basin, France) and the potential sources of these particles (agricultural or forest soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…Fallout radionuclide concentrations measured in the Orge River SPM were reported in a previous paper (Froger et al, 2018) and showed a linear increase in 7 Be and 210 Pb xs activities in SPM collected in downstream direction (Fig. S2).…”
Section: Modeling the Pah Profile Of Urban Particlessupporting
confidence: 73%
See 3 more Smart Citations
“…Fallout radionuclide concentrations measured in the Orge River SPM were reported in a previous paper (Froger et al, 2018) and showed a linear increase in 7 Be and 210 Pb xs activities in SPM collected in downstream direction (Fig. S2).…”
Section: Modeling the Pah Profile Of Urban Particlessupporting
confidence: 73%
“…All river water, atmospheric and road sediments samples were collected in the Orge River catchment, which is located 30 km south of Paris City and drains into the Seine River ( Figure 1; see Froger et al, 2018). Four sampling sites were selected based on their urbanization rate and previous work on the catchment (Le Pape et al, 2012): three were located on the main stem of the Orge River, whereas a fourth site was located on its main tributary, the Yvette River.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Moderately contamination by Cu, Zn, Sb, and Pb, was also found in SPM collected in an urban river in the Orge River catchment (a subcatchment of the Seine River basin located 30-km south of Paris City). [12] The resuspension of SPM previously accumulated in the bottom is another source of HEs in rivers during flood events. [13] Therefore, understanding the distribution and composition of SPM in rivers is, clearly, a matter of high concern.…”
Section: Introductionmentioning
confidence: 99%